Semantics of plant names in Kazakh and Turkish languages - Begimova, G.; Salkarayev, Zh. (Journal of Oriental Studies, 2016)
In the thesis we are studying the ways of formation of plant names. Their importance in people’s life. The role of plant names in the culture of Kazakh and Turkish people. Their believes on plants. The associations with plant names. In what sphere the plant names are used.